Breaking Bad and disabilities: Neo-liberalism, crip studies and critiques of ableism in the classroom. (1st March 2019) - Cordeiro, Will
AMC's hit television series Breaking Bad has a devoted fan base, and critics have explored the show's relationship to television's 'Third Golden Age' through binge-watching, philosophy and sociopolitical crises. Many critics, however, neglect to explore the show's discussion of issues related to disability. Breaking Bad depicts diverse experiences of people with disabilities. The show uses disability as a way to demonstrate how differing philosophical viewpoints about brains and bodies create different identities and different narratives about those identities. This way of uncovering the narratives of the show can be used pedagogically to provide alternatives to a medical model of disability, and explore in the classroom how disability intersects with class, race, gender and other identities.